Power Struggle and New Media Actor Contestation in Indonesia during the Post Pandemic - Santoso, Didik Haryadi; Budianto, Heri; Haq, Naziful (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2023)
In the new media space, narratives and discussions about covid-19 are still ongoing. Virtual audiences debate each other over the discourse that occurs. Research on the Covid-19 discourse has been carried out by many international researchers and Indonesian researchers. However, it is still not clear to the public who and how these actors fight in new media. How is the power struggle and contestation between the actors and those involved? This research uses the web crawler’s method and the SNA (Social Network Analysis) method in collaboration with astramaya.id. Data research is limited to 2019 to 2021 considering and considers the high number of narratives, discourses, and discussions about Covid-19. The results of the study show that the contestation of actor networks in the Covid-19 pandemic discourse is divided into three main actor clusters, namely the government cluster, the scientist and buzzer cluster, and the popular scientific info provider actor cluster. The power struggle occurs in 3 (three) lines, namely the state, the media industry, and social media actors. The fight occurred instantly and pragmatically and, in the end, gave birth to hegemonic discourse and hegemonic actors in the discourse on the post pandemic.